2020
DOI: 10.1111/jgh.15206
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oral‐origin bacteria in the fecal microbiome and albumin–bilirubin grade in patients with hepatitis C

Abstract: Background Bacteria of oral origin (BO) in the gut are associated with prognosis in patients with cirrhosis. The Greengenes database (gg_13_8) is widely used in microbiome analysis, but the expanded Human Oral Microbiome Database (eHOMD), a specialized database for BO, can add more detailed information. We used each database to evaluate the relationship between the albumin–bilirubin grade (ALBI) and the microbiome in patients with hepatitis C. Methods Eighty patients were classified into the low ALBI group (LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Bilirubin is excreted into the intestine and reduced to urobilinoids and/or urobilinogens by gut bacteria (Fahmy et al, 1972; Koníčková et al, 2012; Vítek et al, 2005; Vítek & Tiribelli, 2020; Yamamoto et al, 2021). Interestingly, we observed the enrichment of gut microbes involved in urobilinogen metabolism in the high‐altitude samples (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Bilirubin is excreted into the intestine and reduced to urobilinoids and/or urobilinogens by gut bacteria (Fahmy et al, 1972; Koníčková et al, 2012; Vítek et al, 2005; Vítek & Tiribelli, 2020; Yamamoto et al, 2021). Interestingly, we observed the enrichment of gut microbes involved in urobilinogen metabolism in the high‐altitude samples (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, oral Treponema denticola , together with Porphyromonas gingivalis and Tannerella forsythia , are known as the “red complex” which have been widely considered essential pathogens in periodontal disease etiology and pathogenesis. A series of animal and human studies have confirmed that the genera Fretibacterium ( Yamamoto et al., 2021 ), Propionibacterium ( Del Chierico et al., 2017 ), Shuttleworthia ( Xie et al., 2016 ), Eggerthia ( Yamamoto et al., 2021 ), and Bulleidia ( Bashiardes et al., 2016 )are prevalent in the oral or gut microbiota with liver disease including nonalcoholic fatty liver disease, hepatocellular carcinoma. These findings could be interpreted by the emerging oral-gut-liver axis that oral microbes could translocate into the gastrointestinal tract, where they would spread to the liver and induce hepatic diseases( Imai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the three age groups, differences in significantly changed OTUs and functional pathways in response to PMA treatment were also observed. For these OTUs, previous studies showed that Selenomonas noxia in saliva was associated with refractory periodontitis [ 39 ] and hepatitis C [ 40 ], while Capnocytophaga granulosa was associated with Papillon-Lefèvre syndrome [ 41 ], but the associations of Peptostreptococcaceae_[XI][G-5]_bacterium_HMT_493 , Ottowia sp._HMT_894 , Treponema sp._HMT_238 , Lachnospiraceae_[G-2] bacterium HMT 096 and some other bacteria with diseases were still not clear. Some of these microbes might always come up in a dead form in saliva samples, resulting in a potential bias in analysis of the pathogenic process in the circumstances of diseases.…”
Section: Discussionmentioning
confidence: 99%